Program gerakan literasi di Sekolah Alam Lampung: Model evaluasi menggunakan CIPP - Rita Sari, Rita Sari (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2021)
This study aims to see how this literacy program runs. This study focused on natural schools in Lampung, using the CIPP evaluation model. The method used in this study is a qualitative research method with an evaluation research design by observing, interviewing, and examining program implementation documents. Sources of information were obtained through interviews with the main director, curriculum director, and R&D director. principals, educators and students. The results of the research on the context component show that the CIPP from the Lampung Natural School has been successfully implemented. The literacy program is carried out in stages 1) Habituation. 2) Learning. 3) Development. The three stages are by the guidelines for the School Literacy Movement (GLS). The analogy of the Natural School Curriculum is Morals; Leadership; Logic thinking; Entrepreneurship. The Literacy Program for Reading and Writing at Sekolah Alam Lampung needs an increase in both the collection of non-fiction books, consistency in reading and writing interests for students and teachers, and appropriate qualifications for librarians.